Western Ideological State Apparatuses and Native American Culture in Erdrich’s LaRose - Maqbool, Tabassum; Rakha , Aqsa Allah (Unisia, 2022)
This research sheds light on Western use of educational Ideological State Apparatuses (ISA) as an important weapon to eradicate Native American culture. Although there have been huge research on Native American Culture and Euro-American oppression of Native Americans, very small is known about the ideological method of European oppression. The picture that appears from Louise Erdrich’s LaRose is that for Europeans, education is a tool to enlighten the natives. However, for the natives, education is a process of transforming their culture into Western ideology promoting Western socio-cultural norms. Ideological oppression is more adverse than subdued oppression.  This study analyses Louis Erdrich’s Larose through Althusser’s theory of ISA which means that people are controlled firstly by ideology, then by constraint. Europeans used both suppression and ideology to obliterate their culture by which they could assimilate them, and there would be a minor risk of resistance. As a result, Europeans have tried to eradicate the religion and culture of Native Americans through education to establish their own culture and religion. Louise Eldritch uncovers the dark side of the educational civilization process, which this research shall analyze through Althusser’s theory of ISA.